Flutter prediction, suppression and control in aircraft composite wings as a design prerequisite: a survey - Njuguna, James A. K. (Wiley, 2007)
Emergence of flutter compromises not only the long-term durability of the wing structure, but also the operational safety, flight performance and energy efficiency of the aircraft. Effectual means of flutter prevention are, therefore, mandatory in the certification of new flight vehicles. This work intends to address the flutter phenomenon highlighting the above issues, and reviews some of the most recent theoretical and experimental developments in flutter analyses. In the following subsections, theoretical, computational and experimental flutter for composite structures is pursued. In particular, panel flutter, thrust-induced flutter, wing/store-type flutter, non-linear flutter, damaged panel flutter, flutter in compressed flow and flutter control via neural networks are covered. Effects of fibre/ply orientation on flutter are also briefly covered. The review further looks into aerothermoelastic behaviour of composite structures buckling problem and hopf bifurcation point determination. Analysed flutter of actively/passively controlled composite structures is critically reviewed due to the emphasized importance in modern structures. It is appreciable that the knowledge gained from the study of flexible structures and unsteady airflows in aircraft can be transitioned back to more traditional flutter studies. It is hoped that this review work will stimulate research and collaborations that will lead to significant progress in the understanding of this dynamically rich and potentially important area of enhancement of flutter prediction, suppression and control of active and passive composite aircraft structures. Copyright (C) 2006 John Wiley & Sons, Ltd.